The Influence of the Teams Games Tournament Method on Elementary School Students' Knowledge of Preparedness Eruption Disaster - Nurfinanda, Pipit; Mujito, Mujito (Health Gate, 2023)
Abstract: Preparedness is an activity to anticipate pre-disaster mitigation so that each individual is always ready and prepared to face natural disasters. This study aims to determine the knowledge of school-aged children about pre-disaster preparedness for the eruption of Mount Kelud. This study used a pre-experimental method with a sample size of 31 respondents taken through purposive sampling technique. Data collection was done using a questionnaire. The results of the study showed a significant increase in knowledge. The pre-test results showed that there were no respondents in the good knowledge category, but after being given education using the Time Games Tournament method, there were 23 respondents (74%) in that category. Additionally, the category of sufficient knowledge increased from 0% to 26%, and the category of poor knowledge decreased from 100% to 0%. The Time Games Tournament method is an effective learning technique for delivering pre-disaster preparedness knowledge in a fun way. This method can also increase students' spirit, enable them to actively participate, foster a sense of togetherness and mutual respect, and improve creativity. Therefore, educators and health workers are expected to apply an educational program using the Time Games Tournament learning method in conducting health education. Keywords: preparedness, education, Team Games Tournament method, school age child